Perancangan Game Edukasi Menebak Lirik Lagu-Lagu Daerah Berbasis Unity 2D untuk Platform Android - Achpal Haddid; Maulana Qaedi Aufar; Akbar Ramadhan; Yovi Pratama (TIN: Terapan Informatika Nusantara, 2023)
The development of information and communication technology has had a significant impact on various aspects of life, including in the field of education. One of the increasingly popular uses of technology is the use of educational games to increase interest in learning and understanding material interactively. This study aims to design an educational game based on Unity 2D with the theme "Guess the Lyrics of Regional Songs" for the Android platform. This research uses a new method (GDLC) which consists of six stages of Initiation, Pre-Production, Production, Testing, Beta and Release